2017
DOI: 10.1002/2327-6924.12423
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the factors that influence nurse practitioner transition in Australia

Abstract: Background and purpose Nurse practitioner (NP) legislation was introduced in Australia in 1998 with the first NPs endorsed 2 years later. Although the number of NPs has slowly increased, they still face significant challenges adjusting to their new role. The aim of this study was to explore the factors that influence the experience of new NPs. Methods Ten newly appointed NPs were interviewed three to four times over a 12‐month period. Using a summative content analysis, data were reduced to four key factors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
2
12
0
1
Order By: Relevance
“…A number of participants employ language that emphasizes self-governing and independence when discussing autonomy, while for others, predominantly doctors, autonomous practice is seen as practicing within a limited and defined scope. MacLellan et al (2017) and Hoff et al (2019) found that ANPs often feel frustrated about unnecessary constraints in their capacity to use their training and experience, an idea also identified by Corbally and Lees-Deutsch (2019) who found that, although ANPs are at the peak of their careers, they were clearly frustrated and restricted by constraints placed on their roles.…”
Section: Discussionmentioning
confidence: 83%
“…A number of participants employ language that emphasizes self-governing and independence when discussing autonomy, while for others, predominantly doctors, autonomous practice is seen as practicing within a limited and defined scope. MacLellan et al (2017) and Hoff et al (2019) found that ANPs often feel frustrated about unnecessary constraints in their capacity to use their training and experience, an idea also identified by Corbally and Lees-Deutsch (2019) who found that, although ANPs are at the peak of their careers, they were clearly frustrated and restricted by constraints placed on their roles.…”
Section: Discussionmentioning
confidence: 83%
“…The change from student to graduate nurse has been examined by scholars such as Neishabouri et al 1 and Kaihlanen et al 2. While the shift to new nursing practices has been shown to demands support 3, and advancement to nurse practitioner to entail significant challenges 4, we found no studies on the progression from Registered Nurse (RN) to the more advanced ORN. Therefore, little or no light has been shed on the disparities between ward nurse duties and that of the ORN.…”
Section: Introductionmentioning
confidence: 75%
“…Such micro-level enablers seemed to counter-balance barriers associated with lack of role clarity at the boundary with medicine [54], as well as with other nurses and allied health professionals. Where such barriers exist, there is a risk of sabotage of extended roles due to professional jealousy or perceived threats to role distinctiveness [55].…”
Section: Discussionmentioning
confidence: 99%